Hadiths About Communication Ethics (Study of Hadiths about Responsibility and Maintaining Information Accuracy) - Saiful Bahri (Budapest International Research and Critics University, 2018)
This study was aimed at finding the Hadiths about Communication Ethics. Communication is a complex process that involves behavior and allows individuals to connect with other people and the world around them. Communication in question is Islamic communication, namely communication with the character of al-karimah or ethical. The method of this study the were the content analysis approach, this approach were used to study and analyze existing technical content, then connected with the hermeneutic method. This merger aims to analyze tek Hadith by harmonizing the theme of the ethics of communication.This research is important to be done which is the benefit of finding harmony of Hadith with the constitutional ethics of communication and also an enrichment of knowledge in understanding Hadith by using thematic interpretation methods. Responsibility is found in Imam Bukhari 6605's hadith can be understood in meaningful words